2002
DOI: 10.1128/aac.46.6.1746-1754.2002
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Sequential Intravenous (i.v.) and Oral Moxifloxacin Compared with Sequential i.v. and Oral Co-Amoxiclav with or without Clarithromycin in Patients with Community-Acquired Pneumonia Requiring Initial Parenteral Treatment

Abstract: The objective of the present trial was to compare the efficacy, safety, and tolerability of moxifloxacin (400 mg) given intravenously (i.v.) once daily followed by oral moxifloxacin (400 mg) for 7 to 14 days with the efficacy, safety, and tolerability of co-amoxiclav (1.2 g) administered by i.v. infusion three times a day followed by oral co-amoxiclav (625 mg) three times a day, with or without clarithromycin (500 mg) twice daily (i.v. or orally), for 7 to 14 days in adult patients with community-acquired pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
12

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 18 publications
4
98
1
12
Order By: Relevance
“…Since neither our study not that by Gleason et al were randomised, the patients treated with less common antibiotic schedules might correspond to those with more severe disease or with a greater probability of resistant microorganisms. Interestingly, in a randomised trial Finch et al 27 found that patients treated with a fluoroquinolone (moxifloxacin) had lower mortality and a shorter length of stay in hospital than those treated with a b-lactam with or without a macrolide.…”
Section: Discussionmentioning
confidence: 99%
“…Since neither our study not that by Gleason et al were randomised, the patients treated with less common antibiotic schedules might correspond to those with more severe disease or with a greater probability of resistant microorganisms. Interestingly, in a randomised trial Finch et al 27 found that patients treated with a fluoroquinolone (moxifloxacin) had lower mortality and a shorter length of stay in hospital than those treated with a b-lactam with or without a macrolide.…”
Section: Discussionmentioning
confidence: 99%
“…L'efficacia clinica e la tollerabilità della moxifloxacina nella CAP, nelle AECB e nelle ABS sono state studiate su un numero elevato di pazienti, nel corso di diversi trial multicentrici controllati, nazionali e internazionali, strutturati nella maggior parte come studi in doppio cieco [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118].…”
Section: Efficacia Clinica E Batteriologica Nelle Infezioni Acute Delunclassified
“…We found one multicentre RCT comparing a quinolone (moxifloxacin) versus coamoxiclav (amoxicillin-clavulanic acid). [19] Mortality --No data from the following reference on this outcome. [19] -…”
Section: Quinolones Versus Co-amoxiclav (Amoxicillin-clavulanic Acid)mentioning
confidence: 99%
“…Directness point deducted as low mortality in studies (3.2%) as compared with normally seen in this group (10%), which may affect generalisability Low 0 -1 0 -1 4 Atypical coverage regimens versus non-atypical coverage regimens Clinical cure 25 (5053) [17] Directness points deducted for inclusion of co-intervention (erythromycin) and unclear follow-up Low 0 -2 0 0 4 Penicillin versus cephalosporins Clinical cure 1 (378) [18] Quality point deducted for no intention-to-treat analysis. Directness point deducted for inclusion of co-intervention Clinical cure 1 (480) [19] Quality point deducted for no intention-to-treat analysis Moderate 0 0 0 -1 4 Daptomycin versus ceftriaxone Clinical cure 2 (834) [20] Quality point deducted for group randomisation. Directness point deducted for small number of comparators Low 0 -1 0 -1 4 Early mobilisation versus usual care…”
Section: Benefits and Harmsmentioning
confidence: 99%
See 1 more Smart Citation